Resistance to RHD virus in wild Australian rabbits: Comparison of susceptible and resistant individuals using a genomewide approach. Issue 17 (24th July 2017) - Schwensow, Nina I.; Detering, Harald; Pederson, Stephen; Mazzoni, Camila; Sinclair, Ron; Peacock, David; Kovaliski, John; Cooke, Brian; Fickel, Jörns; Sommer, Simone
Abstract: Deciphering the genes involved in disease resistance is essential if we are to understand host–pathogen coevolutionary processes. The rabbit haemorrhagic disease virus (RHDV) was imported into Australia in 1995 as a biocontrol agent to manage one of the most successful and devastating invasive species, the European rabbit ( Oryctolagus cuniculus ). During the first outbreaks of the disease, RHDV caused mortality rates of up to 97%. Recently, however, increased genetic resistance to RHDV has been reported. Here, we have aimed to identify genomic differences between rabbits that survived a natural infection with RHDV and those that died in the field using a genomewide next‐generation sequencing (NGS) approach. We detected 72 SNPs corresponding to 133 genes associated with survival of a RHD infection. Most of the identified genes have known functions in virus infections and replication, immune responses or apoptosis, or have previously been found to be regulated during RHD. Some of the genes identified in experimental studies, however, did not seem to play a role under natural selection regimes, highlighting the importance of field studies to complement the genomic background of wildlife diseases. Our study provides a set of candidate markers as a tool for the future scanning of wild rabbits for their resistance to RHDV. This is important both for wild rabbit populations in southern Europe where RHD is regarded as a serious problem decimating the prey of endangered predator species and for assessing the success of currently planned RHDV variant biocontrol releases in Australia.